Analysing determinants of match attendance in the European Rugby Cup - Vincent Hogan; Patrick Massey; Shane Massey (University College Dublin, UCD School of Economics, 2012)
The economic literature on professional sports leagues suggests supporters' utility depends on uncertainty of outcome (competitive balance) and the quality of play. Unlike soccer, where the Champions League is dominated by teams from larger countries, our analysis indicates that the ERC exhibits high degrees of both dynamic and inter-league competitive balance. Using data from 1,096 matches played over 17 seasons, we analyse match attendances in the pool stages of the European Rugby Cup (ERC), a competition that involves teams from the three main European rugby leagues. The results indicate that the quality of the home team is the main determinant of match attendances, although a strong visiting team also raises attendances. Medium-term (seasonal) uncertainty, which has received less attention in the literature, appears far more important than short-run (match) uncertainty. Measures designed to make matches more attractive, e.g. bonus points for high scoring, appear to have had little effect on attendances.
Keywords: D12; D21; L22; L23; L83; 330; Professional team sports; competitive balance; consumer demand